Optimized AODV routing protocol based on reverse route search in leisure time and route learning - DU Qing-song1; ZHU Jiang1; ZHANG Er-yang1 (Tongxin xuebao)
An optimized AODV routing protocol（O-AODV） which integrated RRSL mechanism（reverse route search in leisure time） and route learning mechanism was proposed.According to O-AODV,many local routes were produced in MANET and route redundancy was increased,therefore improved the efficiency of routing discovery,speeded up the lo-cal repair procedure of break routes,and decreased the overhead of route rediscovery.Simulation results indicate that O-AODV can improve packet delivery ratio and decrease the end-to-end packet delay,its performance is superior to AODV in large scale and fast changing MANET.